Jak pan Rajewicz do Piotrkowa jechał, czyli o wierszu z rękopisu Działyńskich uwag kilka - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article focuses upon the analysis of poems written down in the manuscript associated with the Działyński family. The works have satirical in nature and are addressed to the circle of the closest people, relatives and family. What is more, their author is using different types of literary styles and literary genres (e.g. prayer, laudatio, speech). The poems have a carnivalesque character. That is why they are upsetting rational order of the world. The author is mocking and unmasking conventions. Of course, the value of these poems should not be overrated. These literary pieces are examples of composition inconsistency and stylistic ineptitude. The article is taking also a matter of the authorship of poems, however, it verifies the authorship of Marcin Działyński, the governor of Nakło.